"It's natural to look for a source": A qualitative examination of alternative beliefs about HIV and AIDS in Cape Town, South Africa. (April 2017) - Rubincam, Clara
This article highlights how African men and women in South Africa account for the plausibility of alternative beliefs about the origins of HIV and the existence of a cure. This study draws on the notion of a "street-level epistemology of trust"—knowledge generated by individuals through their everyday observations and experiences—to account for individuals' trust or mistrust of official claims versus alternative explanations about HIV and AIDS. Focus group respondents describe how past experiences, combined with observations about the power of scientific developments and perceptions of disjunctures in information, fuel their uncertainty and skepticism about official claims. HIV prevention campaigns may be strengthened by drawing on experiential aspects of HIV and AIDS to lend credibility to scientific claims, while recognizing that some doubts about the trustworthiness of scientific evidence are a form of skeptical engagement rather than of outright rejection.